Kworkflow A Linux kernel Developer Automation Workflow System - Tadokoro, David; Siqueira, Rodrigo; Meirelles, Paulo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2025.11322, 2025)
The Linux kernel is a central project to the Free/Libre and Open Source Software (FLOSS) ecosystem. Developers who interact with the kernel source code routinely face a variety of repetitive and error-prone tasks, including setting up testing environments, managing kernel configuration files, compiling with various toolchains, deploying to varied targets, and correctly submitting patches. These tasks, though essential, often require handcrafted scripts that become fragile, difficult to maintain, and disconnected from the core development goals. Kworkflow (kw) is a Developer Automation Workflow System (DAWS) that aims to provide high-quality tools that mitigate known bottlenecks experienced by kernel developers in their daily workflows. It provides a unified Command-Line Interface (CLI) that automates and streamlines many tasks, allowing practitioners to focus more on developing code and less on setup overhead and details. The hub-like design of the project reflects its philosophy of incorporating existing tools to avoid duplication of efforts and wasted resources from the community, a by-product of the many ad-hoc scripts developers commonly create. The kw tool also offers a data collection infrastructure, which makes it an excellent platform for further scientific research in the Linux kernel development model. In this sense, kw serves as a robust tool for real kernel developers and an opportunity for academic research work. Demo video:  Software Heritage permalink [19].